(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the new Conctitution of the Republic of Uzbekistan the introduction of ecological norms, keeping our nature ecologically clean for our population and future generations constitutional rights and obligations to remain, environmental safety guarantees are highlighted.